65. Laser evoked potentials and skin biopsy to evaluate small nerve fiber dysfunction in myotonic dystrophy type 1(DM1): A preliminary study. Issue 12 (December 2017) - Pagliarani, E.; Donadio, V.; Incensi, A.; De Pasqua, S.; Avoni, P.; Liguori, R.
Abstract : Myotonic dystrophy type 1 (DM1) is a multisystem disorder that affects skeletal and smooth muscle as well as the eye, heart, endocrine system, and central nervous system. We recruited 3 patients with previously diagnosed DM1 (mean age was 51 ± 8 years; height 166 ± 8 cm) who underwent leg skin biopsy and laser evoked potentials (LEP). The specific aim of this study is to ascertain the small nerve fiber involvement in DM1 by means of LEP and skin biopsy. Two patents showed abnormalities in both LEP and skin biopsy whereas one patient displayed abnormal skin biopsy but normal findings in LEP. Our data demonstrated a reasonable concordance between LEP and skin biopsy in evaluating small fiber loss in DM1. However, these are preliminary data and a larger number of patients must be recruited before to draw any definite conclusion.